Children's overestimation of performance across age, task, and historical time: A meta‐analysis. - Xia, Mengtian; Poorthuis, Astrid M. G.; Thomaes, Sander (Child Development, 2024)
Children tend to overestimate their performance on a variety of tasks and activities. The present meta‐analysis examines the specificity of this phenomenon across age, tasks, and more than five decades of historical time (1968–2021). Self‐overestimation was operationalized as the ratio between children's prospective self‐estimates of task performance and their actual (i.e., objectively measured) task performance. A total of 246 effect sizes from 43 published articles were analyzed (4277 participants; 49.6% girls; sample mean ages range from 4 to 12; 86.0% of studies conducted in North America or Europe). Children's self‐overestimation was robust across tasks, with their estimates of performance being 1.3 times their actual performance. In addition, children's self‐overestimation decreased with sample age and increased with the year of data collection.